Processing and characterisation of two– and three–phase polymer–based nanocomposites for energy storage applications. (11th December 2012) - Helal, Emna; Ounaies, Zoubeida; Meddeb, Amira B.
The aim of this work is to process and characterise nanocomposites which combine the advantages of a flexible lightweight polymer matrix (polyvinylidene fluoride, PVDF), the high conductivity of single wall carbon nanotubes (SWNTs) and the attractive dielectric properties of titanium dioxide (TiO2 ) nanospheres, to simultaneously achieve improved dielectric constant and low dielectric loss. The effect of nanoparticles and the effect of the heat treatment on the evolution of the phase, crystallinity and dielectric behaviour of the polymer host are investigated. In particular, a transition from γ to α phase due to heat treatment is identified. In addition, the crystallinity of three–phase composites is found to decrease compared to the corresponding two–phase composites indicating a possible interaction between SWNTs and TiO2 nanofillers. Furthermore, an improvement of the permittivity is achieved in all nanocomposites at low frequencies and attributed to interfacial and orientation polarisations and to the heat treatment.